O11.4 Trans and gender diverse people's experiences of sexual health care are associated with sexual health screening uptake. (14th July 2019) - Callander, Denton; Cook, Teddy; Cornelisse, Vincent; Pony, Mish; Duncan, Dustin; Wiggins, Jeremy; Vlahakis, Emanuel; Duck-Chong, Liz; Rosenberg, Shoshana; Holt, Martin
Abstract : Background: Transgender and gender non-binary people have unique sexual health needs and rates of HIV and other sexually transmissible infections that outstrip the general population. Very little is known, however, about their experiences of sexual health care, including how those experiences might affect sexual health screening practices. Methods: Using data collected via a national survey of transgender and non-binary people in Australia (n=1, 636), responses to four items on sexual health care experiences were summed to create a scale from 0 (gender-sensitive) to 4 (gender-insensitive). Bivariate and multivariate analyses compared scale scores and assessed associations with sexual health screening. Results: In total, 50% of trans and non-binary participants were uncomfortable disclosing their gender during sexual health care, 68% reported that intake paperwork did not allow accurate gender descriptions, 74% felt staff made assumptions about their bodies or sex lives, and 40% did not receive sexual health care that was sensitive to their needs. On average, non-binary participants experienced the greatest degree of gender-insensitivity (M=2.3) compared with transgender men (M=1.8) and women (M=1.6, p<0.001). Gender insensitivity was most common in hospitals (M=2.9) followed by general practice clinics (M=2.1) and least common in sexual health clinics (M=1.6) and community-lead sexual health services (M=1.3, p<0.001). Among sexually active participants, 51% had received a sexual health screen in the previous year. After controlling for confounders (age, education, income, monogamy, condom use), transgender and non-binary people with more gender-insensitive experiences of sexual health care were less likely to report a recent sexual health screen (adjusted odds ratio=1.3, 95% confidence interval:1.1–1.5, p<0.001). Conclusion: Transgender and, in particular, non-binary people experience gender insensitivity when receiving sexual health care, most notably in hospital settings. This insensitivity is associated with delaying sexual health screens among the sexually active. Educating health providers on gender sensitive sexual health care could improve screening uptake. Disclosure: No significant relationships.